Upregulation of bcl-2 is involved in the mediation of chemotherapy resistance in human small cell lung cancer cell lines - Sartorius, Ute; Krammer, Peter H. (International journal of cancer, 2002)
Chemotherapeutic drugs eliminate cancer cells by induction of apoptosis. Resistance to chemotherapy is partly due to a decreased apoptosis rate. Here we investigated resistance to anticancer drugs in 9 small cell lung cancer (SCLC) cell lines. Apoptosis was induced by cisplatin, doxorubicin and etoposide and was found to be independent of caspase-8 expression. Since caspase-8 is essential for signal transduction of death receptor-mediated apoptosis, all known death receptor systems are thus not required for drug-induced apoptosis in SCLC. Furthermore, we found that anticancer drugs could activate the mitochondrial pathway of apoptosis without involvement of upstream caspases. Finally, by culturing 3 sensitive cell lines in subtherapeutic concentrations of etoposide, resistant cells were generated that exhibit cross-resistance to cisplatin and doxorubicin. Drug resistance was paralleled by strong upregulation of Bcl-2, which diminished apoptosis by inhibiting the loss of the mitochondrial transmembrane potential and the release of cytochrome c. The role of bcl-2 in these processes was supported by bcl-2 transfection and antisense inhibition. These results indicate that Bcl-2 contributes to drug resistance in SCLC, a finding that has profound therapeutic implications. © 2001 Wiley-Liss, Inc.
First published: 01 November 2001
Gesehen am 14.04.2021